The Impact of the SARS-Cov2 Pandemic on a Persuasive Educational Antimicrobial Stewardship Program in a University Hospital in Southern Italy: A Pre-Post Study - Margherita Macera (MDPI AG, 2021)
Objectives: We evaluated the effect of the pandemic on the disruption of a persuasive educational antimicrobial stewardship program (ASP) conducted in a university hospital in southern Italy. Methods: In March 2020, the ASP, which began in January 2017 and was carried out at different times in 10 wards, was stopped due to the COVID-19 pandemic. We conducted an observational study with interrupted time series analysis to compare the antibiotic consumption and costs, average length of hospital stay and in-hospital mortality between 12 months before and 9 months after the interruption. Results: Four medical, four surgical wards and two ICUs were included in the study, for a total of 35,921 patient days. Among the medical wards we observed after the interruption a significant increase in fluoroquinolone use, with a change in trend (CT) of 0.996, p = 0.027. In the surgical wards, we observed a significant increase in the overall consumption, with a change in level (CL) of 24.4, p = 0.005, and in the use of third and fourth generation cephalosporins (CL 4.7, p = 0.003). In two ICUs, we observed a significant increase in piperacillin/tazobactam and fluoroquinolone consumption (CT 9.28, p = 0.019, and 2.4, p = 0.047). In the wards with a duration of ASP less than 30 months, we observed a significant increase in antibiotic consumption in the use of piperacillin/tazobactam and fluoroquinolones (CT 12.9, p = 0.022: 4.12, p = 0.029; 1.004, p = 0.011). Conclusions: The interruption of ASP during COVID-19 led to an increase in the consumption of broad-spectrum antibiotics, particularly in surgical wards and in those with a duration of ASP less than 30 months.